Expert assessment of the need to improve the management of physical culture and sports at the local level - Dorofieieva, Tatiana (Slobozhanskyi Herald of Science and Sport, 2022)
Purpose: to determine an expert assessment of the need to improve the management of physical culture and sports at the local level, namely in the regions and territorial communities. Material and methods: expert survey by questioning in digital and correspondence format. To create an expert group, scientific and pedagogical workers were interviewed. 38 correctly completed questionnaires were received, which were filled in by 38 scientists (doctors of sciences, professors) from specialized institutions of higher education and faculties of physical education. Results: an expert assessment was given by the statement included in the questionnaire, aimed at establishing the attitude of leading scientists to improving the management of physical culture and sports at the local level. On all claims, the experts expressed support for improving the management and use of research results. In this case, it is recommended to use the achievements of sports science as an important trigger for increasing the level of management of sports development. Conclusions: 97.4% (of which 81.6% completely agree and 15.4% rather agree) of the experts expressed that the level of management significantly determines the state of sports development and the quality of physical culture and sports services at the local level. 89.5% (50% and 39.5%) of experts agree with the statement that the level of management of sports development at the local level is insufficient. 95.7% (65.8% and 28.9%) of the respondents agree that there are significant reserves for improving the management of sports development at the local level. 100% of respondents (84.2% and 15.8%) support the opinion that sports science should be involved in improving the management of sports development at the regional and community level. 100% (81.5% and 18.4%) believe that the introduction of high-quality scientific developments into practice will improve the management of sports in the regions. As you can see, the opinion that the management of sports development at the local level requires significant changes and qualitative improvement was fully confirmed by experts. Keywords: expert assessment, management, development of physical culture and sports at the local level, the use of research results.